Erik af Pommerns erhvervelse af København fra roskildebiskoppen: Et overgreb mod kirkens frihed, eller afklaringen af et gammelt mellemværende? - Knudsen, Anders Leegaard (Kirkehistoriske Samlinger, 2013)
Erik af Pommern overtog i 1417 besiddelsen af København fra Roskilde bispestol. Der har i dansk forskning været næsten fuldstændig enighed om at se denne overtagelse som en krænkelse af biskoppens ejendomsret til byen og borgen, kun retshistorikeren Poul Johs. Jørgensen har tolket kongens overtagelse som værende i overensstemmelse med lovens bogstav, hvis ikke dens ånd. I senere forskning medførte det dog kun, at overtagelsen blev set som et raffineret juridisk spil, snarere end som et klodset magtmisbrug. En ny undersøgelse bekræfter og udbygger Jørgensens tolkning og viser tillige, at Københavns forhold til kongemagten og Roskilde bispestol indtil Erik af Pommerns tid ikke var så klart, som det siden er blevet opfattet. Set i det lys virker overtagelsen ikke som et entydigt overgreb, tværtimod synes kongen ikke blot at have stået juridisk stærkt, men også ud fra en rimelighedsbetragtning at have haft en god sag. Summary In 1416, Erik VII “of Pomerania”, king of Denmark, Sweden and Norway, sued the episcopal see of Roskilde for possession of the city and castle of Copenhagen. In early February 1417, a court of arbitration, consisting of an equal number of ecclesiastical and lay members of the Council of the Realm, awarded the king possession until the right of ownership could be determined in the subsequent proceedings which were scheduled to follow. These proceedings never took place, however, as the bishop refused to participate and possession of Copenhagen was maintained by King Erik and subsequent Danish kings in the face of repeated attempts by the bishops to recover it. The Reformation in 1536 and the Crown’s subsequent confiscation of Church lands settled the matter permanently. To a surprising degree, Danish historians have agreed in seeing King Erik’s action as frivolous and the outcome of the proceedings as a miscarriage of justice. The sole exception has been the legal historian Poul Johannes Jørgensen, who in 1939 gave a clear and full exposition of the legal framework of the action and argued that the king actually had a better case than otherwise assumed. While his exposition of the legal framework has met with general acceptance, historians continue to see the outcome of the proceedings as having been based on might rather than right and thus as having been predetermined. The present article seeks to place the case in its proper perspective by looking at the history of the contested possession of Copenhagen. It also returns to the question of the legal framework in light of recent research and looks more deeply into the countermeasures of the Church, viz. the documents prepared for submission at the proceedings. Sometime between 1157 and 1167, the bishop of Roskilde received Copenhagen as a gift from the Danish king. Whether the bishop then proceeded to build a castle or the gift included an existing castle is a moot point. Copenhagen Castle was never just a private castle, but an important element in the defence of the realm and the royal gift to the bishop of Roskilde must have carried the responsibility to aid and support the king in war and other emergencies. For the better part of a century, this seems to have caused no problems; but during the dynastic troubles in the latter half of the thirteenth and the early part of the fourteenth centuries, the bishops often failed to live up to that responsibility. They were, in fact, often among the kings’ enemies and the kings out of necessity seized the castle on several occasions. With the accession to the throne of Waldemar IV in 1340 the relationship between the Crown and the bishop improved and the bishop was a staunch supporter of the king during one of the direst moments of Danish history when most of the realm was mortgaged to the Counts of Holstein. The redemption of these mortgages turned out to be a long drawn-out affair, and possession of Copenhagen was crucial to the king’s success. The Crown’s interest in Copenhagen had so far been primarily military, but King Waldemar’s reign marked a shift with economic interests becoming increasingly important. The bishop gave King Waldemar possession of Copenhagen from 1341, being amply compensated for his loss, and the king retained it until his death in 1375 after which the bishop recovered it, again with amble compensation for losses incurred. He and his successors retained it until 1416, when, on the death of the incumbent bishop, King Erik launched his successful attempt to acquire Copenhagen. At the core of the lawsuit lay the manner in which the bishop had recovered Copenhagen in 1375. The written agreement between the king and the bishop had neither specified an expiration date for the king’s possession of Copenhagen, nor prescribed how (and indeed if) it should revert to the bishop. The matter was thus open to discussion. The legal framework was expertly analysed by Poul Johannes Jørgensen, and recent research in Danish legal history has if anything merely strengthened his views. Danish law favoured the possessor to an extent which seems foreign to modern eyes, and once the king was awarded possession of the castle and city, he was virtually impossible to evict from it. The crux of the matter was, therefore, the question of who should have possession. The bishop had undeniably been in possession of Copenhagen, but his death had left the castle in the care of a trustee until a new bishop had been elected and consecrated. It was a legal masterstroke for the king to have the castle sequestered until the question of right of possession had been determined, and although this procedure has generally been regarded as devious, as a ploy, it was in accordance with Danish law. In fact the procedure had been used once before with regard to Copenhagen, in 1343, in connection with the settlement of territorial disputes between the Danish and Swedish kings and thus did not constitute a break with legal precedents. Once the king had Copenhagen in his possession, the bishop would have to prove that he had a better title. He could not do this, as it turned out, having no title deed per se but only a series of papal confirmations of his predecessors’ rightful ownership, as well as a few settlements and agreements, none of which proved of any value in documenting a superior title to Copenhagen. King Erik, on the other hand, had few documents, but they were central to his claim that King Waldemar had had Copenhagen in rightful possession and that it had not reverted to the bishop in the lawful manner. The failure of modern historiography to draw the full consequences of Poul Johannes Jørgensen’s article as well as the failure to see the acquisition of Copenhagen in its true historical perspective have led to the somewhat anachronistic view that this acquisition constituted a violation of the Church’s supposedly absolute right of ownership. On the contrary, the acquisition seems neither unwarranted nor unlawful, but rather like the settlement of a recurring difference between the Crown and the Church.